2017
DOI: 10.1089/jwh.2016.6003
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Time to Endometriosis Diagnosis in the United States

Abstract: Time to endometriosis diagnosis appears to have shortened in the US. Better patient and physician education regarding symptomatology may contribute to further gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 30 publications
11
87
0
3
Order By: Relevance
“…By shifting the paradigm to the patient rather than the lesion, the path to clinical diagnosis has the potential to be more inclusive with reduced diagnostic delay. Indeed, Soliman et al 18 reported diagnosing endometriosis by nonsurgical methods shortened the mean time from first consultation to diagnosis compared with surgical diagnosis. This shift, however, requires clinical diagnostic methodologies that accurately identify endometriosis.…”
Section: Argument For Clinical Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…By shifting the paradigm to the patient rather than the lesion, the path to clinical diagnosis has the potential to be more inclusive with reduced diagnostic delay. Indeed, Soliman et al 18 reported diagnosing endometriosis by nonsurgical methods shortened the mean time from first consultation to diagnosis compared with surgical diagnosis. This shift, however, requires clinical diagnostic methodologies that accurately identify endometriosis.…”
Section: Argument For Clinical Diagnosismentioning
confidence: 99%
“…Although a detailed review of endometriosis in adolescents is beyond the scope of this discussion, it is noteworthy that endometriosis occurs in adolescents and that patients who are younger at the time of symptom onset experience longer diagnostic delays than older patients. 17,18 This delay is attributed to prolonged time before seeking treatment and a longer interval between first clinical consultation and referral or diagnosis. It is important that clinicians evaluate symptoms that merit suspicion in adolescents as seriously as in adults.…”
Section: Ajogorgmentioning
confidence: 99%
See 2 more Smart Citations
“…For practical and economic reasons, this is not always possible, which could be a factor behind the observed diagnostic delay, especially in primary care [1]. The delay can be up to 10 years from symptom onset to diagnosis [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%